2009
DOI: 10.1111/j.1532-950x.2009.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Propofol–Xylazine and the Anderson Sling Suspension System for Recovery of Horses from Desflurane Anesthesia

Abstract: Technique choices to facilitate individualized, atraumatic recovery of horses from general anesthesia are desirable. Use of IV propofol and xylazine to transition horses from desflurane anesthesia during sling recovery to standing posture may facilitate improved recovery management of high-injury risk equine patients requiring general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…In the present study, it was hypothesized that the quality of recovery from anesthesia after administration of propofol would be better than that after administration of the other 2 drugs, as suggested by results of some studies. 25,49,50 We also hypothesized that propofol administration would be associated with a shorter recovery time because of its pharmacokinetic profile. 51 However, no significant difference in recovery quality or recovery time was evident among the 3 drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was hypothesized that the quality of recovery from anesthesia after administration of propofol would be better than that after administration of the other 2 drugs, as suggested by results of some studies. 25,49,50 We also hypothesized that propofol administration would be associated with a shorter recovery time because of its pharmacokinetic profile. 51 However, no significant difference in recovery quality or recovery time was evident among the 3 drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…When an infusion of xylazine and ketamine was used to modulate recovery from isoflurane anesthesia in horses, 10 the overall mean score for recovery quality (2.0) was similar to that of the present study. Other studies 14,15 in horses have revealed that apnea was commonly associated with xylazine-propofol infusions following desflurane anesthesia. The same may not be true for desflurane anesthesia followed by an infusion of xylazine-propofol, which was associated with a mean recovery quality score of 1.2 (ie, an almost excellent recovery).…”
Section: Discussionmentioning
confidence: 95%
“…10,14,15 After disconnection from the anesthetic breathing circuit, each horse received supplemental oxygen, insufflated at 15 L/min via the endotracheal tube, as long as it remained in lateral recumbency. Each horse was briefly hoisted so that the thick pad could be removed; each horse was then carefully lowered and repositioned in left lateral recumbency on the floor of the recovery stall, at which time videotape recording of the recovery from anesthesia commenced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steffey et al . showed that horses placed in the AS after 4 h of desflurane anaesthesia had low arterial oxygen pressure (PaO 2 ). Since these horses received xylazine and a propofol constant rate infusion during sling recovery, the question remains whether hypoxaemia resulted from pharmacologically induced respiratory depression or from adverse mechanical effects of the sling on breathing and regional blood flow.…”
Section: Introductionmentioning
confidence: 99%